Influencia del liderazgo visionario en el desarrollo organizacional / The Influence of Visionary Leadership on Organizational Development - Ramos, Luis; Díaz Lara, Belkis (Impacto Científico, 2020)
Resumen El proposito de este articulo es analizar la influencia del liderazgo visionario en el desarrollo organizacional. Se realizó una revision documental de autores como Álvarez y col. (2001); Bennis (1998); Carrero (2001); Céspedes y col. (2006). Chiavenato (1998), Gibson y col. (2003), Peter y Col. (1997), Robbins y Couter (2004), entre otros, asi como el analisis de las diferentes definiciones del desarrollo organizacional y el liderazgo visionario. Se concluye que el liderazgo visionario mejora el rendimiento del talento humano y desarrolla su potencial, la comunicación interna efectiva, fomenta el liderazgo efectivo, facilita la motivacion y creatividad, aumenta la retroalimentacion, mejorando las relaciones entre los miembros de la organización reforzando la autoestima. Lo cual genera un desarrollo organizacional de vanguardia. Abstract The intention of this article is to analyze the influence of visionary leadership on organizational development. A documentary review was performed of authors such as Álvarez, S. et al (2001), Bennis, W. (1998), Carrero, C. (2001), Céspedes D., Rocco A. and Fuentes R. (2006), Chiaventato, I. (1998), Gibson et al (2003), Peter M. Senge et al (1997), Robbins, S. and Couter, M. (2004), Stoner, J., Freeman, R. and Gilbert, D., among others, as well as the analysis of different definitions of organizational development and visionary leadership. Conclusions were that visionary leadership improves the performance of human talent and develops its potential, improves effective internal communication, foments effective leadership, facilitates motivation and creativity, increases feedback, improving relations between organization members and reinforcing self-esteem, generating organizational development in the vanguard.